Die präskriptive Norm und die Entwicklungstendenzen in der Deklination des Substantivs im gegenwärtigen Deutsch - Darski,, Józef Paweł (Studia Germanica Posnaniensia, 2018)
The author presents noun inflection in the present-day standard German and discusses the way in which the present prescriptive norm was established. This norm is not always in line with developmental tendencies of the noun declension. If one stuck strictly to the noun declension in German in singular it would be uniformed in the same way as noun declension in plural.